Teachers’ Professional Development and Its Influence on Teaching Innovation in Rural Schools - Muh Habibulloh (International Journal of Multidisciplinary Research and Innovation, 2025)
This study explores the relationship between teachers’ professional development and teaching innovation in rural schools located in Ambon, Indonesia. The research aims to understand how structured training, peer collaboration, and reflective teaching practices influence the ability of rural educators to implement innovative strategies in their classrooms. Employing a qualitative case study approach, data were collected through in-depth interviews with 12 teachers and 3 school principals from four rural schools in the region. Thematic analysis revealed that continuous professional development particularly in the areas of ICT integration, contextualized pedagogy, and curriculum adaptation has a significant impact on teachers’ creativity and willingness to innovate. The findings indicate that teachers who regularly engage in professional learning communities and receive consistent institutional support are more likely to experiment with student-centered learning models, problem-based learning, and culturally responsive teaching. This study highlights the importance of sustainable teacher development policies and tailored support systems to foster educational innovation in under-resourced areas.